Pergeseran Kekuatan Akta Autentik Serta Kewenangan Notaris Dalam Pembuatan Akta Pendirian Koperasi (Pasca Putusan Mahkamah Konstitusi No. 28/PUU-XI/2013) - Muhammad Gondo Ratangin (Lex Renaissance, 2017)
AbstractThis study describes the legal force Establishment of Cooperative deed of Notary after the Constitutional Court ruling No. 28 / PUU-XI / 2013, as well as analyzing the legal implications of the Minister of Cooperatives and SMEs towards authority in making Cooperation Deed Notary. This research is a field research by using juridical empirical approach. The study concluded, first: the power of cooperative law deed of Notary after the Constitutional Court ruling No. 28 / PUU-X / 2013 resulted in a shift in the regulations regarding cooperatives for the time that is returned to Act No. 25 of 1992 concerning Cooperatives until enactment of the new law. Therefore, the whole procedure and the establishment of cooperatives from the date of repeal of Act No. 17 of 2012 concerning Cooperatives by the Constitutional Court back in Act No. 25 of 1992 concerning Cooperatives and all implementation regulations. Secondly, the implications of Ministerial Decree No. 98 / KEP / M.KUKM / IX / 2004 regarding Notary Public as Cooperation Deed, making Notary public official authority in this case to serve the public in the process of making authentic evidence in accordance with the authority granted by UUJN- P, is limited, because the authority of the notary is a deed authentic under the Act, unless another Specifies Act.Keywords: Notary, NPAK, cooperatives, shift deeds, deed of cooperation